KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI PERSAMAAN LINGKARAN KELAS XI MIA SMA - Rusmanda, Cicik Muspar; Hamdani, Hamdani; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to determine students' mathematical communication skills on the material in the circle equation of class XI MIA SMA Negeri 7 Pontianak. The research method is quantitative Â descriptive and the research design is a survey. The subjects of this research were 33 students of class XI MIA 1 of SMA Negeri 7 Pontianak. Data collection techniques used were direct measurement and communication techniques. Data collection tools used were test questions and interview guidelines. The results of the research generally showed that students' mathematical communication skills were obtained by 60% in the medium category. This can be seen based on indicators of students' ability to state the situation of the equation of a circle in the form of images and express it into their own language through writing is 62% with a high category, and indicators of the ability of students to express the daily events of the equation of a circle into a mathematical symbol and solve it through writing is 57% in the medium category.